2015
DOI: 10.1371/journal.pone.0133601
|View full text |Cite
|
Sign up to set email alerts
|

Pneumococal Surface Protein A (PspA) Regulates Programmed Death Ligand 1 Expression on Dendritic Cells in a Toll-Like Receptor 2 and Calcium Dependent Manner

Abstract: Pneumonia leads to high mortality in children under the age of five years worldwide, resulting in close to 20 percent of all deaths in this age group. Therefore, investigations into host-pathogen interactions during Streptococcus pneumoniae infection are key in devising strategies towards the development of better vaccines and drugs. To that end, in this study we investigated the role of S. pneumoniae and its surface antigen Pneumococcal surface protein A (PspA) in modulating the expression of co-stimulatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…We also demonstrated that the route of calcium entry regulated the survival of macrophages during M. tb and HIV co-infection [14]. Additionally, we also showed that calcium homeostasis regulated the expression of T cell inhibitory molecule PD-L1 on dendritic cells during Streptococcus pneumonia infection [15].…”
Section: Introductionmentioning
confidence: 62%
“…We also demonstrated that the route of calcium entry regulated the survival of macrophages during M. tb and HIV co-infection [14]. Additionally, we also showed that calcium homeostasis regulated the expression of T cell inhibitory molecule PD-L1 on dendritic cells during Streptococcus pneumonia infection [15].…”
Section: Introductionmentioning
confidence: 62%
“…pertussis in the expression of PD-L1 on these antigen presenting cells. This has previously been described for Streptococcus pneumoniae , that was shown to regulate PD-L1 expression on DCs in a TLR2 dependent manner [53]. Co-culture experiments using moDCs and T cells are required to determine whether these emerging strains indeed steer T cells towards a regulatory phenotype.…”
Section: Discussionmentioning
confidence: 83%
“…Autophagy is a recently recognized innate defence mechanism that acts as an autonomous system of the cell for eliminating intracellular pathogens and also plays a role in regulating immune responses to pathogens [ 37 ]. We have recently shown the role of M .…”
Section: Resultsmentioning
confidence: 99%
“…A major defence mechanism of M . tb in macrophages is the prevention of fusion between phagosomes and lysosomes that allows the pathogen to establish long-term persistent infections [ 37 ]. It has also been demonstrated that phagosome-lysosome fusion is mediated by calcium homeostasis [ 38 ].…”
Section: Resultsmentioning
confidence: 99%